Investigating The Problems Faced By Final-Year Students In Writing The Thesis Through Consultation Services At CV. Kiki Areski Kampus - Nurwaliyah Dwi Arhama; Sukardi Weda; Iskandar (International Journal of Language, Education, and Literature, 2025)
The thesis is a final assignment that is required for final-year students to obtain a bachelor's scholarship degree. For most final-year students, this is a big obstacle in getting through the final-years of college. Not a few final-year students face problems in the thesis writing process. But of course, they also look for solutions to these problems. For this reason, researchers are interested in investigating the problems faced by final-year students through thesis guidance services used through CV. Kiki Areski Campus, to find out more clearly students' perceptions regarding the problems they face, to find out what services they get when participating in online thesis guidance services, and to find out more about students' perceptions regarding the quality of guidance services at CV. Kiki Areski Campus uses qualitative methods with a descriptive approach. The research results show two general problem perceptions regarding the problems faced in the final year student thesis writing process, namely internal problems and external problems. Specifically, internal problems are divided into: Lack of motivation, lack of self-confidence, difficulty managing time, and confusion in determining methods, then externally divided into: Limited guidance activities and distraction from the surrounding environment. Second, there are six perceptions about the form of service provided at CV.Kiki Areski Campus towards its participants is: More flexible, more responsive, guides well, provides encouragement, more detail and more comfort. Third, there are four participants' perceptions of the quality of guidance services at CV. Kiki Areski Campus, namely: Problems can be solved, respond quickly, according to the advertisement, and have experienced tutors. Therefore, many final students use online thesis guidance services like this because they are thought to better impact service users